Glossopharyngeal neuralgia associated with cardiac syncope: Two case reports and literature review. (2015) - Krasoudakis, Antonios; Anyfantakis, Dimitrios; Hadjipetrou, Athanasios; Kastanakis, Miltiades; Symvoulakis, Emmanouil K.; Marathianos, Stavros
Highlights: Glossopharyngeal neuralgia is a rare craniofacial syndrome sometimes associated by syncope. A synthesis on topics such as pathogenesis, diagnosis and management is presented. A high levels of awareness for diagnosis and management is required from surgeons. Abstract: Introduction: Vago-glossopharyngeal neuralgia is an unusual clinical syndrome characterized by paroxysms of sharp pain in the distribution of glossopharyngeal nerve. Rarely the condition is associated with arrhythmia and cardiac syncope, a phenomenon named vagoglossopharyngeal neuralgia. Presentation of Cases: Here we present two patients with glosopharyngeal neuralgia associated with repetitive episodes of syncope referred from their primary care physician to neurosurgery department of a general hospital in Crete, Greece. The patients were successfully treated with microvascular decompression. Discussion: A literature review on pathogenesis, diagnosis and management is also performed. Conclusions: Surgeons as well as primary care physicians have to be aware of this rare condition in order to prevent associated life-threatening complications and improve patient's clinical status with accurate therapy.